2020
DOI: 10.5897/jmpr2019.6846
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant and cytotoxic activites and chemical profile of species of Miconia Ruiz Pav., Clidemia D. Don and Tibouchina Aubl. (Melastomataceae)

Abstract: The resistance of microorganisms to current antimicrobials, and the deleterious effects caused by the excessive free radical manufacturing in the human body and their relationship with increasing global incidence of cancer, has led to a continuous search for new chemical agents that can contribute to the fight against these ills. The objective of the present work was to evaluate the antimicrobial, antioxidant and cytotoxic activities and determine the chemical profile of ethyl acetate extract of ten species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Phytochemical evaluations of species of Melastomataceae have revealed the presence of phenolic compounds, triterpenes, steroids, anthocyanins, saponins, organic acids, tannins, anthraquinones and benzoquinones among their constituents as secondary metabolites (Jones et al, 1980;Santos and Tavares, 2003;Serna and Martínez, 2015;Bomfim et al, 2020). The solvent and extractive method used can influence variation in the levels of total phenols and total flavonoids present in extracts (Oliveira et al, 2016), as well as in biological activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phytochemical evaluations of species of Melastomataceae have revealed the presence of phenolic compounds, triterpenes, steroids, anthocyanins, saponins, organic acids, tannins, anthraquinones and benzoquinones among their constituents as secondary metabolites (Jones et al, 1980;Santos and Tavares, 2003;Serna and Martínez, 2015;Bomfim et al, 2020). The solvent and extractive method used can influence variation in the levels of total phenols and total flavonoids present in extracts (Oliveira et al, 2016), as well as in biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance reading of the samples was performed at 620 nm with a UV-Vis spectrophotometer. The same preparation conditions were used to construct the calibration curve for gallic acid (y = 3.8883x + 0.11141; R 2 = 0.9954) (Bomfim et al, 2020). The results were expressed in milligrams of gallic acid per gram of crude extract (mg EAG/g of extract).…”
Section: Phytochemical Profilementioning
confidence: 99%
See 2 more Smart Citations
“…Another study, carried out by Narasimham, et al (2017), demonstrated anti-cancer activity of diluted ethanolic extract of Clidemia hirta leaves against cells of the Dalton Lymphoma Ascites (DLA) lineage. Bomfim, et al (2020) verified antimicrobial activity by the disk diffusion test of the ethyl acetate extract of the aerial parts of C. hirta against M. luteus, S. aureus, and P. aeruginosa, with halos of 13.0 ± 1.02, 9.0 ± 0.57, and 10.0 ± 1.52 mm, respectively, antioxidant activity by the DPPH method (63.54 ± 1.46%) and high toxicity against Artemia salina (LC50 75.8 μg / ml).…”
Section: Introductionmentioning
confidence: 99%